APPLYING TWO STAY TWO STRAY (TSTS) TECHNIQUE BY USING PICTURE SERIES TO IMPROVE STUDENTS’ SPEAKING SKILL AT THE SECONDGRADE IN MAN 2 PAREPARE - Rasdiana Rasdiana; Abu Bakar Juddah; Hamzah Selle (Institut Agama Islam Negeri Parepare, 2019)
The purpose of this research was positively to find out whether applying two stay two stray technique by using picture series to improve students’ speaking skill at the second grade in MAN 2 Parepare. The results of this research, the benefit for the teacher and students. The teacher will be conscious that it is important to apply the technique in teaching. The students can enjoy the lesson so they can be easier to express their ideas and also confidence to speak by using the gesture.The subject of this research is XI MIA 1 class which is consisted of 27 students. The sample was taken by using purposive sampling. The design in this research was pre-experimental with pre-test and post-test design. The student did the pre-test, got the treatment and did the post-test. It aimed to know whether applying two stay two stray technique by using picture series can improve students’ speaking skill.The result in this research was indicated that the improvement of the students’ speaking skill. It was indicated by the students’ mean scoreof post-test (72.26) was greater than pre-test (44.46). Even, for the level significant (p) 5% and df = 26, and the value of table is 1.706, while the value of t-test is 18.34. It means that the t-test value is greater than t-table (2.29 ≥ 1.706). Thus, it can be concluded that the students’ speaking skill is significantly better after getting the treatment. So, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted.